Pelaksanaan Program Redistribusi Tanah Di Kawasan Tanah Adat Provinsi Papua - Yudhistira Setya Wardhana (Universitas Muhammadiyah Purwokerto, 2020)
Agrarian reform or Agrarian Reform as an issue, is complex and multidimensional which is a major program of the Indonesian state in realizing the welfare of the Indonesian people, especially in terms of increasing access of poor peasants to land tenure in Indonesia, but implementing agararial reform is not an easy thing, with many obstacles, both from the legal, land administration, social, political, cultural and security aspects. Agrarian Reform (Agrarian Reform) or land reform is one of the effective tools or ways to achieve successful development, because access to land is fundamental for socio-economic development, poverty reduction, and environmental sustainability, apart from being a factor of production, land is also a factor of wealth, prestige and strength or power. In this perspective, land redistribution not only results in an increase in economic assets owned by poor farmers, but also an increase in political power and social participation, thus, the implementation of agrarian reform is not only aimed at reducing poverty and unemployment, but also in order to eliminate inequality, especially in political and social fields. The Land Redistribution Program in Papua Province itself, as the author sees its implementation, does not pay attention to regulations higher than Presidential Decree Number 86 of 2018.This is also reinforced by Article 18B paragraph (2) of the 1945 Constitution which states that the state recognizes and respects customary law community units. along with their traditional rights as long as they are still alive and in accordance with the development of society and the principles of the Unitary State of the Republic of Indonesia. In addition, Article 3 of the UUPA does contain the term